Socio Juridical Review Of The Criminal Action Of Embraction Of Fiduciary Objects (Case Study Of Kabila District, Bone Bolango District ) - Hadrian Abdjul (Estudiante Law Journal, 2023)
This research aim to find out Socio - juridical review of the crime of embezzlement of Fiduciary Guarantee objects . This study raises two issues, namely how the socio-juridical review of the crime of embezzlement of Fiduciary Guarantee objects and what are the causative factors. This study uses an empirical legal research method with a sociological jurisprudence approach . The results of this study indicate that the socio-juridical review of the crime of embezzlement of Fiduciary Guarantee objects in Kabila District, Bone Bolango Regency is based on the socio-juridical scope, namely, first the law, Second , state institutions that function to form or make and enforce the law , and Third , the interactive relationship between the formal legal system and the legal order of society. Factors causing the crime of embezzlement of Fiduciary Guarantee objects, namely First, economic factors, where the provision of fees is one of the reasons KN is willing to lend his identity to be used in Fiduciary Guarantee agreements by AHI. The second is the social environmental factor, where the friendship relationship that exists between the perpetrators of embezzlement of Fiduciary Guarantee objects is one of the reasons KN is willing to lend his identity to be used by AHI in the Fiduciary Guarantee agreement.